Study on Forecasting Method of Runoff Recession in Dry Season in Lincang City - ZHANG Zhenjie; LI Cheng; LI Zengguo (Renmin Zhujiang)
The runoff of rivers in the dry season in Lincang is mainly replenished by the storewater in the basin, and a generally stable regression law is found in the flow. In recent years,the drought in Lincang City is prone to occur with high frequency. In 2010, there was the mostserious drought in a century. It is particularly important to make a good forecast of recession inthe dry season, master the law of recession, and provide a prediction of water volume in the dryseason for the government decision of urban water supply and agricultural drought resistance.Taking the analysis of recession law of Xihe (2) hydrological station as an example and combiningwith the hydrological characteristics of river runoff in Lincang City, this paper introduces twoforecasting methods of recession in dry season, that is, seasonal recession curve and thecorrelation analysis of runoff before and after the season. Compared with other methods, the twomethods do not require a large number of historical data samples. The methods are simple, easy tomaster, and reliable in prediction results, which are suitable for wide application inhydrological stations and reservoir stations of small and medium river with short observationperiod in Lincang City, and of guiding significance for scientific scheduling and droughtresistance of reservoirs in dry season.